EKSPLORASI MODEL TINGKAT KECELAKAAN LALU - Haryadi, Bambang (Jurnal Teknik Sipil dan Perencanaan, 2011)
Abstract: The objectives of the presents study wasÃÂ  to explore mathematical models that could be usedÃÂ  toÃÂ  estimateÃÂ  theÃÂ  numberÃÂ  ofÃÂ  accidentsÃÂ  onÃÂ  interurbanÃÂ  tollÃÂ  roads.ÃÂ  PreditiveÃÂ  modelsÃÂ  were developedÃÂ  byÃÂ  relatingÃÂ  trafficÃÂ  exposureÃÂ  (averageÃÂ  dailyÃÂ  trafficÃÂ  andÃÂ  roadÃÂ  sectionÃÂ  length)ÃÂ  withÃÂ  the numberÃÂ  ofÃÂ  accidentsÃÂ  perÃÂ  unitÃÂ  ofÃÂ  time.Accident,ÃÂ  roadwayÃÂ  sectionÃÂ  andÃÂ  trafficÃÂ  volumeÃÂ  dataÃÂ  were obtainedÃÂ  fromÃÂ  Jagorawi,ÃÂ  JakartaCikampek,ÃÂ  padaleunyi,ÃÂ  andÃÂ  palikanciÃÂ  tollÃÂ  road.ÃÂ  AccidentÃÂ  rate models were developed from those data usingÃÂ  generalized linear modelling (GLM) techniques. The conclusionsÃÂ  fromÃÂ  theÃÂ  study were:ÃÂ  (1)ÃÂ  linierÃÂ  regression model wasÃÂ  notÃÂ  appropriateÃÂ  toÃÂ  beÃÂ  usedÃÂ  to predictÃÂ  accidentsÃÂ  number,ÃÂ  becauseÃÂ  accidentÃÂ  occurenceÃÂ  didÃÂ  notÃÂ  followÃÂ  normalÃÂ  distribution,ÃÂ  (2) Poisson regression possessed accident occurence characteristics: descrete, rare and random, and (3)ÃÂ  NegativeÃÂ  BinomialÃÂ  distributionÃÂ  wasÃÂ  moreÃÂ  appropriateÃÂ  toÃÂ  representÃÂ  accidentÃÂ  occurence phenomenon with overdispersion. Keywords: accident rate, generalized linear modelling, Poisson regression, nagative binomial regression. ÃÂ Abstrak: PenelitianÃÂ  iniÃÂ  bertujuanÃÂ  untuk mengeksplorasi model matematisÃÂ  yangÃÂ  dapatÃÂ  digunakan untukÃÂ  meramalkanÃÂ  jumlahÃÂ  kecelakaan,ÃÂ  padaÃÂ  suatuÃÂ  ruasÃÂ  jalanÃÂ  tolÃÂ  antarÃÂ  kota.ÃÂ  ModelÃÂ  prediksi dikembangkanÃÂ  denganÃÂ  menghubungkanÃÂ  paparanÃÂ  lalulintas,ÃÂ  yangÃÂ  dinyatakanÃÂ  denganÃÂ  volume lalulintas dan panjang ruas jalan, dengan keselamatan, yang dinyatakan dalam jumlah kecelakaan per satuan waktu. DataÃÂ  jalan, kecelakaan, danÃÂ  lalulintas selama duaÃÂ  tahun, diambil dariÃÂ  jalanÃÂ  tol antarÃÂ  kotaÃÂ  Jagorawi,ÃÂ  Jakarta0Cikampek,ÃÂ  PadaleunyiÃÂ  danÃÂ  Palikanci.ÃÂ  ModelÃÂ  tingkatÃÂ  kecelakaan dikembangkan dari data tersebut dengan teknik generalized linear modelling (GLM), dan dikalibrasi denganÃÂ  menggunakanÃÂ  teknik0teknikÃÂ  statistik.ÃÂ  BeberapaÃÂ  kesimpulanÃÂ  yangÃÂ  dapatÃÂ  ditarikÃÂ  dari penelitianÃÂ  iniÃÂ  adalah:ÃÂ  (1)ÃÂ  ModelÃÂ  regresiÃÂ  linierÃÂ  denganÃÂ  distribusiÃÂ  normalÃÂ  tidakÃÂ  memadaiÃÂ  untuk memprediksiÃÂ  kecelakaan;ÃÂ  tingkatÃÂ  kecelakaanÃÂ  tidakÃÂ  terbuktiÃÂ  mengikutiÃÂ  distribusiÃÂ  normal;ÃÂ  (2) PenggunaanÃÂ  regresi PoissonÃÂ  lebih mencerminkan karakteristik kejadian kecelakaan: diskrit, acak, langka;ÃÂ ÃÂ ÃÂ  danÃÂ  (3)ÃÂ  DistribusiÃÂ  BinomialÃÂ  NegatifÃÂ  palingÃÂ  baik merepresentasikanÃÂ  kejadianÃÂ  kecelakaan dengan adanya gejala overdispersi pada data. Kata kunci: tingkat kecelakaan, generalized linear modelling, regresi poisson, regresi binomial negatif.